Indonesian Preference of Teleconsultation Modality: Qualitative Study - Ria Wibowo, Yossico; Djunita Pasaribu, Rina (International Journal of Science, Technology & Management, 2024)
Since the outbreak of the COVID-19 pandemic, telemedicine users throughout the world have increased, including in Indonesia. Since COVID-19 pandemic, telemedicine is a business platform in the health sector with increasing number of users. Minister of Health Regulation Number 20 of 2019, which is currently the basis for implementing telemedicine in Indonesia, does not regulate the use of teleconsultation media used for diagnosis on telemedicine platforms. This research aims to provide recommendations regarding the use of teleconsultation media on telemedicine platforms. In this study, data was obtained from interviews with thirty-three participants. In conclusion, the video call feature should be a mandatory modality for teleconsultation, but it is optional to use and with adjusted teleconsultation fees.